2022
DOI: 10.3389/fpsyg.2022.953959
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in professional drivers’ fatigue level measured with BAlert mobile app: A psychophysiological, time efficient, accessible, and innovative approach to fatigue management

Abstract: Addressing fatigue is useful in a variety of scenarios and activities. Fatigue has recently been studied from a psychophysiological standpoint. As a result, the expression and impact of peripheral and central fatigue has been evaluated. Driving is one occupation where tiredness has disastrous consequences. BAlert is a smartphone app that approaches exhaustion with psychophysiological measures. More specifically, it evaluates the level of fatigue via heart rate variability (HRV) data and the cognitive compromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…The previous result may happen due to the sense of responsibility the married had; however, married drivers mostly have children, so they almost will drive safely than singles for their family's sake [39], [40]. Simultaneously, normally married women are older than single women, so by default, considering a self-as enterprising driver will be less among older female drives [39], [41], [42]. On the contrary, a finding from a study done previously indicated that adolescent and young adult females are involved in risky driving behavior because they are often supposed to be prone to traffic violations [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous result may happen due to the sense of responsibility the married had; however, married drivers mostly have children, so they almost will drive safely than singles for their family's sake [39], [40]. Simultaneously, normally married women are older than single women, so by default, considering a self-as enterprising driver will be less among older female drives [39], [41], [42]. On the contrary, a finding from a study done previously indicated that adolescent and young adult females are involved in risky driving behavior because they are often supposed to be prone to traffic violations [37].…”
Section: Discussionmentioning
confidence: 99%
“…The age of drivers is another important factor that can affect involvement in risky driving behaviors [42], [43]. The majority of participants have a good speed attitude when driving on highways and outside the cities, with a 97.3% prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Individual subject and day were set as random effects. As previous studies have reported that sex, 22 age, 23 commute time 24 and valence to WREC 4 are associated with outcomes (eg, fatigue, sleep and recovery), these variables were included in the fixed effects as covariates. For days when the participants chose 'I worked from home all day', the commute time was set to 0 hour.…”
Section: Analysesmentioning
confidence: 99%